2020
DOI: 10.1002/jso.26239
|View full text |Cite
|
Sign up to set email alerts
|

A novel preoperative risk score to optimize patient selection for performing concomitant liver resection with cytoreductive surgery/HIPEC

Abstract: Background: While parenchymal hepatic metastases were previously considered a contraindication to cytoreductive surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC), liver resection (LR) is increasingly performed with CRS/HIPEC. Methods: Patients from the US HIPEC Collaborative (2000-2017) with invasive appendiceal or colorectal adenocarcinoma undergoing primary, curative intent CRS/HIPEC with CC0-1 resection were included. LR was defined as a formal parenchymal resection. Primary endpoints were posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Combined CRS–HIPEC and liver resection can be an alternative for patients with limited diseases, leading to an improvement in terms of survival compared to patients who could receive only systemic therapy ( 42 , 44 ). Despite the feasibility and safety of the combined LR and CRS–HIPEC in metastatic CRC reported from several studies ( 20 , 22 , 23 , 27 , 33 , 36 , 37 , 39 , 45 ), data on the matter show conflicting results, with updated studies and meta-analyses demonstrating evidence to the contrary ( 5 , 21 , 32 , 34 , 46 ). Razenberg et al ( 47 ) reported a significantly lower median OS in patients with concomitant PC + LM treated with palliative chemotherapy compared to the patients treated with CRS and HIPEC (12.5 vs. 23.1 months).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Combined CRS–HIPEC and liver resection can be an alternative for patients with limited diseases, leading to an improvement in terms of survival compared to patients who could receive only systemic therapy ( 42 , 44 ). Despite the feasibility and safety of the combined LR and CRS–HIPEC in metastatic CRC reported from several studies ( 20 , 22 , 23 , 27 , 33 , 36 , 37 , 39 , 45 ), data on the matter show conflicting results, with updated studies and meta-analyses demonstrating evidence to the contrary ( 5 , 21 , 32 , 34 , 46 ). Razenberg et al ( 47 ) reported a significantly lower median OS in patients with concomitant PC + LM treated with palliative chemotherapy compared to the patients treated with CRS and HIPEC (12.5 vs. 23.1 months).…”
Section: Discussionmentioning
confidence: 99%
“…However, there could be a biased selection in interpreting this result as no data regarding the two groups (dissemination of the disease, history prior to treatment, and general conditions of the patients) were available. Lo Dico et al ( 39 ), in their multicenter study, showed that extended surgical management with curative resection plus HIPEC in selected patients with PM + LM is feasible with acceptable morbidity and mortality rates (31% and 4%, respectively) and a better OS. These results are probably associated with a better selection of patients and with the choice of performing the combined procedure only if a minor LR was required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations